The Practices of HRM, Human Capital, and Organizational Performance: A Literature Discussion in SME Context - Jonner Simarmata (Universitas Batanghari, 2020)
SMEs are a very important economic sector in almost all countries. Not only in developed countries but also in developing countries. The reason is, this sector contributes greatly to economic growth, especially to the GDP and employment. Therefore, all governments give a big support to the growth of this sector to contribute even more. The purpose of organizations including SMEs is to increase value for their stakeholders. Therefore, every manager tries hard to improve the performance of his company. In theory, one of the factors that influence organizational performance is HRM practice (Armstrong & Taylor, 2014). However, experts argue that the relationship of HRM practices with organizational performance is an indirect relationship. Therefore, it is important to think about what variables can mediate this relationship. In the literature it is mentioned that human capital can act as a mediating variable in the relationship between HRM practices and organizational performance. However, in the context of SMEs, studies on human capital as a mediator are still rarely found. This present article aims to add to the literature on the mediating role of human capital in the relationship of HRM practices with organizational performance in the context of SMEs.